1962
DOI: 10.1192/bjp.108.457.772
|View full text |Cite
|
Sign up to set email alerts
|

Broken homes among attempted suicides and psychiatric out-patients: A comparative study

Abstract: Many investigators have pointed out the social and psychological meanings of broken homes and their effects on individuals' behaviour. Goldfarb (3) stressed the importance of normal parental relationships both in ego formation and in the transfer of ego functions from parent to child. Thompson (16) maintains that the loss of a familiar perceptual framework may be as equally important as the loss of a love-object. Bowlby (2) points out that love deprivation and superficial relationships frequently lead to malad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

1963
1963
1991
1991

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(18 citation statements)
references
References 10 publications
2
16
0
Order By: Relevance
“…In findings reported elsewhere it was pointed out that two-thirds of this group also came from broken homes (Bruhn, 1962). Thus, it seems that coming from a broken home is not in itself so significant as the repetition of a similar disorganizing event later in life.…”
Section: Ile I Sex and Age Of Attempted Suicide Cases And Edinburgh Rmentioning
confidence: 56%
See 1 more Smart Citation
“…In findings reported elsewhere it was pointed out that two-thirds of this group also came from broken homes (Bruhn, 1962). Thus, it seems that coming from a broken home is not in itself so significant as the repetition of a similar disorganizing event later in life.…”
Section: Ile I Sex and Age Of Attempted Suicide Cases And Edinburgh Rmentioning
confidence: 56%
“…Although the broken home is important, it is only one of a constellation of aetiological factors contributing to attempted suicide. In a recent study regarding broken homes among attempted suicides it was found that the broken home becomes causally significant only when other indications of social disorganization are also found (Bruhn, 1962).…”
Section: Resultsmentioning
confidence: 99%
“…Lendrum (1933) found 22.6% of attempted suicides were unemployed compared with 12.2 % in the local population. Bruhn (1962), in Edinburgh, reports that 43 % of parasuicides were unemployed compared with 17 % among a control group of nonparasuicidal psychiatric out-patients, and less than 4% for the general population of the city.…”
Section: Discussionmentioning
confidence: 94%
“…(5) The number of children in the 1971 group was small according to Ulster standards, and was smaller than in women investigated in our other studies. (6) In both groups between one half and two thirds of patients were admitted to the hospital for the first time. (7) There was no significant difference be tween the two groups in respect of the number of their suicidal attempts.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing a group of 91 patients who attempted suicide with a group of matched psychiatric patients who had not attempted suicide, Bruhn [1962] found the prevalence of the following factors in the sui cidal group: (a) residential mobility, (b) brief stay at the current address, (c) household instability, and (d) marital disharmony. All these factors were very much in evidence in both our groups of patients.…”
Section: Residential Mobilitymentioning
confidence: 99%